Finite Math and Applied Calculus (6th Edition)

Published by Brooks Cole
ISBN 10: 1133607705
ISBN 13: 978-1-13360-770-0

Chapter 0 - Section 0.3 - Multiplying and Factoring Algebraic Expressions - Exercises - Page 21: 22



Work Step by Step

Distribute using terms of the first parentheses: $...=x^{3}(3x^{2}-x+2)-2x^{2}(3x^{2}-x+2)+4(3x^{2}-x+2)$ $=3x^{5}-x^{4}+2x^{3}-6x^{4}+2x^{3}-4x^{2}+12x^{2}-4x+8$ gather like terms: $-x^{4}-6x^{4}=-7x^{4}$ $+2x^{3}+2x^{3}=4x^{3}$ $-4x^{2}+12x^{2}=8x^{2}$ $=3x^{5}-7x^{4}+4x^{3}+8x^{2}-4x+8$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.